2010
DOI: 10.1123/jsm.24.5.502
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Fuzzy Logic to Service Quality Research: A Case of Fitness Service

Abstract: This research focused on measuring perceived quality in the context of sport and fitness services using a novel approach in sport management: fuzzy logic. Several analytical procedures have been depicted to operate with fuzzy techniques, which may be applied to empirical research by a wide range of researchers in the sport literature, as well as sport managers. This study showed that fuzzy logic is an attractive method to increase the value of the information collected from customers' evaluations. The implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 65 publications
1
24
0
7
Order By: Relevance
“…This indicator can be assessed positively by operators of the resort, but should be analyzed with care, since this positive value may be subject to change. Furthermore, as Martinez, Ko and Martinez [55] concluded that an attribute which can be interpreted as a positive aspect to a customer does not necessarily mean a positive perception of organization quality. Moreover, considering tourists who have visited other resorts, they have mentioned little satisfaction with services provided.…”
Section: Discussionmentioning
confidence: 99%
“…This indicator can be assessed positively by operators of the resort, but should be analyzed with care, since this positive value may be subject to change. Furthermore, as Martinez, Ko and Martinez [55] concluded that an attribute which can be interpreted as a positive aspect to a customer does not necessarily mean a positive perception of organization quality. Moreover, considering tourists who have visited other resorts, they have mentioned little satisfaction with services provided.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the studies in sports are as follows: Novatchkov and Baca [ 15 ] designed a fuzzy logic model for the assessment of strength training exercises in sports. Martínez et al [ 16 ] proposed a fuzzy logic approach for measuring perceived quality in terms of sport and fitness services. Şahin and Erol [ 17 ] designed a fuzzy logic model for forecasting demand of soccer games.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Martinez et al (2010) determined that one of the most important problems being faced by modern sport marketeers was the service quality providing the following arguments: the proxy measure of management performance;an important factor in positioning the company; andan essential determinant of customer behaviour variables such as customer loyalty.…”
Section: Introductionmentioning
confidence: 99%